Actinomycin D downregulates Sox2 and improves survival in preclinical models of recurrent glioblastoma. Issue 9 (30th March 2020) - Taylor, Jessica T; Ellison, Stuart; Pandele, Alina; Wood, Shaun; Nathan, Erica; Forte, Gabriella; Parker, Helen; Zindy, Egor; Elvin, Mark; Dickson, Alan; Williams, Kaye J; Karabatsou, Konstantina; et al.
Abstract: Background: Glioblastoma (GBM) has been extensively researched over the last few decades, yet despite aggressive multimodal treatment, recurrence is inevitable and second-line treatment options are limited. Here, we demonstrate how high-throughput screening (HTS) in multicellular spheroids can generate physiologically relevant patient chemosensitivity data using patient-derived cells in a rapid and cost-effective manner. Our HTS system identified actinomycin D (ACTD) to be highly cytotoxic over a panel of 12 patient-derived glioma stemlike cell (GSC) lines. ACTD is an antineoplastic antibiotic used in the treatment of childhood cancers. Here, we validate ACTD as a potential repurposed therapeutic for GBM in 3-dimensional GSC cultures and patient-derived xenograft models of recurrent glioblastoma. Methods: Twelve patient-derived GSC lines were screened at 10 µM, as multicellular spheroids, in a 384-well serum-free assay with 133 FDA-approved compounds. GSCs were then treated in vitro with ACTD at established half-maximal inhibitory concentrations (IC50 ). Downregulation of sex determining region Y–box 2 (Sox2), a stem cell transcription factor, was investigated via western blot and through immunohistological assessment of murine brain tissue. Results: Treatment with ACTD was shown to significantly reduce tumor growth in 2 recurrent GBM patient-derived models and significantly increased survival. ACTD is also shown to specifically downregulate the expression of Sox2 both in vitro and in vivo. Conclusion: These findings indicate that, as predicted by our HTS, ACTD could deplete the cancer stem cell population within the tumor mass, ultimately leading to a delay in tumor progression. Key Points: 1. High-throughput chemosensitivity data demonstrated the broad efficacy of actinomycin D, which was validated in 3 preclinical models of glioblastoma. 2. Actinomycin D downregulated Sox2 in vitro and in vivo, indicating that this agent could target the stem cell population of GBM tumors.